Pneumonia a neglected disease: A mixed-method study on the case-finding program in Indonesia - Sulistyawati Sulistyawati; Liena Sofiana; Sholehatun Khairul Amala; Rokhmayanti Rokhmayanti; Fardhiasih Dwi Astut; Desi Nurfita (AIMS Press, 2020)
Pneumonia eradication program has been implemented, but the incidence rate remains high. This research aims to evaluate the Pneumonia finding program in Sleman district of Indonesia. A mixed-method using sequential explanatory design was conducted during July-August 2019. Input, Process and Output were used as the evaluated methods. Input component were human resource quality, facilities, infrastructure and funding. Process aspect was planning, implementation, monitoring and evaluation. Output was the Pneumonia finding coverage. The quantitative study that employed a survey was done among the Pneumonia officer in 25 primary health centres in the research area. Qualitative study used a semi-structured interview to explore the Pneumonia officer's opinion about the case finding program. Analysis was performed in two stages: 1) Quantitative analysis was started with input data to the spreadsheet, clean the data, and classify into the cut-off. 2) Qualitative analysis was done using a content analysis approach. Input and process found sufficient. But we found poor in the output (Pneumonia finding coverage). Pneumonia finding program has not executed as the expected. The coverage was inadequate since only one out 25 reaches the target of Pneumonia finding coverage. Pneumonia is considered not severe disease become a reason for the inadequate coverage.